Application of the Christiansen Dividing-wall Column Configuration for Multicomponent System Separation - Goran Lukač; Ivan Bilmez; Igor Dejanović (Kemija u Industriji)
Dividing wall distillation columns (DWC) represent a significant advancement in the process industry, promoting sustainability and reducing overall CO2 emissions in continuous separation processes. Currently, DWC applications are mostly limited to three-product configurations, with a single known commercial implementation for four products in the so-called Kaibel configuration, which uses a single vertical dividing wall. While this simplified structure offers advantages in terms of implementation, its structural limitations lead to a reduced degrees of freedom for process control. This limitation is particularly evident in the main fractionator, where the central section between the two side products must operate in total reflux mode. Maintaining this mode in practice can be challenging, especially during process disturbances, often resulting in degraded quality of the two side products. To address this operational issue, a novel configuration is proposed, featuring a horizontal partition between the two side products, and a heat exchanger to maintain thermal coupling between the newly formed sections of the main fractionator. This configuration, referred to as the “|- column” in the literature, was first introduced by Atle C. Christiansen. It effectively eliminates remixing of the middle components, and allows for additional introduction or removal of thermal energy, enabling both sections of the prefractionator to operate near their optimal conditions. Theoretically, this enables more flexible column operation and decoupling of the two sections. In this work, steady-state simulation results of both column configurations are compared using detailed distillation models. A multicomponent hydrocarbon mixture containing 15 components is used as a separation example, with separation into four products.